The effect of viewing-only, reaching, and grasping on size perception in virtual reality - Caterina Foglino; Tamara Watson; Niklas Stein; Patrizia Fattori; Annalisa Bosco (PLoS ONE, 2025)
In virtual environments (VEs), distance perception is often inaccurate but can be improved through active engagement, such as walking. While prior research suggests that action planning and execution can enhance the perception of action-related features, the effects of specific actions on perception in VEs remain unclear. This study investigates how different interactions – viewing-only, reaching, and grasping – affect size perception in Virtual Reality (VR) and whether teleportation (Experiment 1) and smooth locomotion (Experiment 2) influences these effects. Participants approached a virtual object using either teleportation or smooth locomotion and interacted with the target with a virtual hand. They then estimated the target’s size before and after the approach by adjusting the size of a comparison object. Results revealed that size perception improved after interaction across all conditions in both experiments, with viewing-only leading to the most accurate estimations. This suggests that, unlike in real environments, additional manual interaction does not significantly enhance size perception in VR when only visual input is available. Additionally, teleportation was more effective than smooth locomotion for improving size estimations. These findings extend action-based perceptual theories to VR, showing that interaction type and approach method can influence size perception accuracy without tactile feedback. Further, by analysing gaze spatial distribution during the different interaction conditions, this study suggests that specific motor responses combined with movement approaches affect gaze behaviour, offering insights for applied VR settings that prioritize perceptual accuracy.